When the heart deceives: a case report of hyperthyroidism disguised as STEMI in female pregnant patient - Kevin Wibawa; Lidia Debby Wiyono; Raditya Dewangga; Arief Sumarna; Wizhar Syamsuri; Yandi Ariffudin; Suhendiwijaya Suhendiwijaya; Pangeran Akbar Syah (The Egyptian Heart Journal)
Abstract Background Acute myocardial infarction during pregnancy is a rare condition with an incidence of 1 to 10 per 100,000 deliveries. ST-elevation myocardial infarction (STEMI) is dominating the clinical presentation. It is estimated that 29% of the patients had normal coronary arteries, and hyperthyroidism may be associated with coronary vasospasm. Case Presentation: A 30-year-old pregnant woman was referred with inferior STEMI post-failed fibrinolytic therapy. Her hospitalization course was complicated by non-sustained ventricular tachycardia and cardiogenic shock. Coronary angiography revealed normal coronary arteries without intracoronary thrombus, coronary dissection, or coronary atherosclerotic lesion. Laboratory test showed high Free T4 2.71 ng/dL and low TSH < 0.05 mlU/mL. Patient’s condition and hospitalization course were significantly improved after the initiation of hyperthyroid therapy. We suspected a hyperthyroid-induced coronary vasospasm as a potential etiology of myocardial infarction with non-obstructive coronary artery (MINOCA) in this patient. Conclusion Although MINOCA due to hyperthyroidism is a rare finding among pregnant young woman, recognizing this etiology is a paramount of importance due to improved survival with appropriate and specific therapy.